Supply chain contract mechanism under bilateral information asymmetry. (November 2017) - Wang, Xinhui; Guo, Hongmei; Wang, Xianyu
Highlights: We model a supply chain with bilateral asymmetric information of production cost and risk aversion degree. We design the innovative transfer payments relevant to the announced information and the profit allocation rule. With the wholesale price contract, the manufacturer and the retailer both announce a higher information type. With the coordinating contract, the manufacturer and the retailer announce information truthfully. The contract's efficiency is relevant to the expected value of information and the true information. Abstract: In this paper, we investigate the problem of designing a mechanism under a bilateral asymmetric information structure. More specifically, we consider a supply chain consisting of one risk-neural manufacturer and one risk-averse retailer, they have private information regarding the manufacturing costs and degree of risk aversion, respectively. We firstly construct a model under the bilateral information asymmetry using the M-V approach. We then provide a wholesale price contract under bilateral information asymmetry to examine if the true information is revealed. We find that the manufacturer and the retailer overstate their information to gain more individual profit. To achieve the coordination, we propose an innovative coordinating contract mechanism, which contains the trading quantity, the transfer payments, and the profit allocation rules. With this coordinating contract, the manufacturer and the retailer announce their true private information and maximize their expected individual profit as well as the supply chain's profit. We find that the private information of risk aversion degree doesn't affect the supply chain performance under the coordinating contract. Further, the implementation of the contract is relevant to the two parties' profits and to the difference between the expected value of information and the true information. Finally, the numerical examples are presented to illustrate the main results.